DECLARATIVE SENTENCES AS EMOTIONAL NARRATIVES - Fitra, Muh. Al Fachrizah; Sari, Ulvah; Qalbi, Chairunnisa Nurul (SIGEH ELT : Journal of Literature and Linguistics, 2025)
This study analyzes the function of declarative sentences in constructing emotional narratives within the lyrics of "August" by Taylor Swift. This study exploits a descriptive qualitative methodology with a discourse analysis approach to inspect the implication of declarative structures in showing profound emotional themes such as longing, loss, regret, and unrequited love, transcending their grammatical function. Unlike interrogative or imperative forms, declarative sentences within the song express personal veracity and emotional reflections, allowing listeners to connect with the narrative as an array of introspective memories. This study classifies declarative sentences into five functional categories: descriptive, reflective, situational, conclusive, and existential, each enhancing dissimilar aspects of narrative and emotional resonance. The results expose that declarative sentences present as appliances for transmitting information and as rhetorical tools that enhance emotional closeness between the narrator and the audience. Taylor Swift's lyrics design a poetic monologue that captivates listeners, intertwining personal narrative with universal emotional depth. The research prior discourse analysis, stylistics, and popular music studies by illustrating how grammatical structure can impart huge emotional and narrative meaning in contemporary songwriting.